2013
DOI: 10.32607/20758251-2013-5-4-94-105
|View full text |Cite
|
Sign up to set email alerts
|

Polyreactive Monoclonal Autoantibodies in Multiple Sclerosis: Functional Selection from Phage Display Library and Characterization by Deep Sequencing Analysis

Abstract: Multiple Sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system that primarily affects young and middle-aged people. It is widely accepted that B lymphocyte activation is required for MS progression. Despite the fact that the exact triggering mechanisms of MS remain enigmatic, one may suggest that MS can be induced by viral or bacterial infection in combination with specific genetic and environmental factors. Using deep sequencing and functional selection methodologies we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Autoantibody-driven pathogenesis was first implicated by the detection of OCBs and the presence of class-switched autoantibodies in lesions and CSF of MS patients 11,20,22,75,76 . In contrast to autoimmune diseases classically considered to be autoantibody-mediated, such as MG or Grave's disease 77 , where the nature of the autoantigens targeted by autoantibodies is often known, the molecular targets and pathogenic role of autoantibodies in MS patients are still not fully resolved, with some notable exceptions such as in neuromyelitis optica 1 (NMO).…”
Section: Antibody-dependent Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibody-driven pathogenesis was first implicated by the detection of OCBs and the presence of class-switched autoantibodies in lesions and CSF of MS patients 11,20,22,75,76 . In contrast to autoimmune diseases classically considered to be autoantibody-mediated, such as MG or Grave's disease 77 , where the nature of the autoantigens targeted by autoantibodies is often known, the molecular targets and pathogenic role of autoantibodies in MS patients are still not fully resolved, with some notable exceptions such as in neuromyelitis optica 1 (NMO).…”
Section: Antibody-dependent Mechanismsmentioning
confidence: 99%
“…However, unlike what is observed in NMO and MG, there is significant heterogeneity in the antigen specificity of these oligoclonal antibodies, which may target pathogens as well as autoantigens 8 . Multiple studies have demonstrated the presence of clonally expanded B cells within lesions, as well as TLOs, and B cells can be found within the parenchyma, CSF, and meninges of patients with multiple sclerosis [15][16][17][18][19][20][21][22][23][24] . The clinical success of B cell depleting therapies such as anti-CD20 monoclonal antibodies (mAbs) corroborated these results, solidifying the contribution of B cells in the pathogenesis of multiple sclerosis [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Кроме описанных выше CD8 + Т-клеток с двойным TCR [12], у пациентов с РС выделены клоны полиреактивных или перекрестнореагирующих АТ, распознающих одновременно вирусные белки и аутоантигены [18]. Установлено, что два перекрестнореагирующих антигена у разных больных могут связываться легкими или тяжелыми цепями Ig.…”
Section: особенности иммунной реактивности против вирусов при рсunclassified
“…Previously, we have shown that monoclonal human anti-myelin basic protein (MBP) immunoglobulins (IgGs) from MS patients are also reactive toward Epstein–Barr virus (EBV) latent membrane protein 1 (LMP1) (17). Recently, we reported that described molecular mimicry in MS patients is not unique but rather should be extended to a variety of viral and bacterial peptides (18, 19). The aim of the present study was to investigate (i) the possibility of developing myelin-reactive autoantibodies in response to viral antigen LMP1, (ii) whether such response is a characteristic of organisms predisposed to autoimmune abnormalities, and (iii) how the manner of contact with an antigen can affect development of cross-reactive antibodies.…”
Section: Introductionmentioning
confidence: 99%